Unspecified severe mental and behavior disorder associated with puerperium (postpartum psychosis) in posterior reversible encephalopathy syndrome: a case report - Herlimus, Fransiskus T.; Wardani, Ida Aju K.; Widyadharma, I. Putu E. (International Journal of Research in Medical Sciences, 2021)
Postpartum psychosis (PP) is the most severe peripartum mood disorder. PP incidence is rare and affecting about 0.1-0.2% of postpartum mothers. Many factors aggravate the mental condition of the mothers after the labor, including posterior reversible encephalopathy syndrome (PRES) that can cause the new mother suddenly become shocked. In this case report, a 21 years old married housewife was referred from Mangusada regional general hospital with complaints of sadness and restlessness (screaming). During history taking, the patient often screamed that she wants to see her child, she feels uncomfortable, and wants to die if it continued like this (unable to see and move at all). These complaints occurred at 8 days post-cesarean section. The patient couldn’t sleep, had any appetite, and restless for 2 days. The patient had much thought about her child’s condition and herself, but not clearly understood. Neurological examination found GCS E4V5Mx, visual acuity 1/300 ODS and weakness on all four extremities. The mental status examination found improper general appearance, looks sad, inadequate eye contact, mixed type insomnia, hypobulia, and raptus. The patient was diagnosed with unspecified severe mental and behavior disorder associated with puerperium (postpartum psychosis), given haloperidol tablet 0.75 mg every 12 hours orally and the non-pharmacological therapy was family psychoeducation and supportive psychotherapy. PRES can cause a mother stressful enough to manifest PP, it should be treated as early as possible to achieve complete recovery.